Implementasi Sistem Informasi Geografis Pemantauan Perkembangan Gizi Balita di Kabupaten Bireuen - Mutasar, Zakial Vikki, T Irfan Fajri, Chaeroen Niesa, Zulfikar (Jurnal Elektro dan Informatika, 2021)
Bireuen district has seventeen sub-districts with each sub-district centralized in public health services, namely the puskesmas, one of which aims to guarantee and monitor the nutritional health of children under five in Bireuen district.This research was conducted to design a geographic information system that can provide information about thedistribution of under-five nutrition in Bireuen Regency. Geographic information system is a system where mapping of theearth is carried out using a computer, in this case, such as recording the distribution of the location of the Public HealthCenter and Posyandu, Bireuen Regency. The system design uses a web-based program, namely PHP which is supportedby a My-SQL database and mapping using the Google Maps API which is easy to access by the library in data manipulation. The results of the implementation of the system can be input, display search results such as village data, posyandu data, nutritional data on body weight, nutritional data for height, nutritional data, weight or height can also display reports. With the geographical information system on the distribution of nutrition, it can add information for monitoring the nutritional status of children under five in Bireuen Regency.